Method for preparing high-purity graphite through ultrasonic-assisted coupling aluminum salt-complexing agent two-stage impurity removal

Through the ultrasound-assisted aluminum salt-complexing agent two-stage impurity removal method, the problems of high energy consumption and high risk in traditional graphite purification are solved, the green preparation of high-purity graphite is achieved, the purity and specific surface area of ​​graphite are improved, and energy consumption and environmental impact are reduced.

CN120793920APending Publication Date: 2025-10-17YUNNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511143799.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-15
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing graphite purification methods have problems of high energy consumption, high risk and low environmental protection, especially the traditional acid leaching process, which leads to high energy consumption and difficulty in subsequent waste acid treatment.

Method used

The ultrasound-assisted coupled aluminum salt-complexing agent two-stage impurity removal method is adopted. Aluminum salt is added under acidic conditions to generate hydroxyaluminum complex to adsorb F-, and complexing agents such as EDTA are added under alkaline conditions to form stable complexes with Ca2+ and Mg2+. The surface passivation layer of impurities is stripped off by combining ultrasonic enhancement means to achieve deep purification.

Benefits of technology

The fixed carbon content of microcrystalline graphite has been significantly improved, environmental impact and safety risks have been reduced, purity has been increased to over 99.5%, energy consumption has been reduced by 67%, wastewater can be simply treated to meet discharge standards, and particle size has been refined to significantly increase specific surface area.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120793920A_ABST
    Figure CN120793920A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing high-purity graphite through ultrasonic-assisted coupling aluminum salt-complexing agent two-stage impurity removal, and belongs to the technical field of natural microcrystalline graphite purification. The method comprises the following steps: mixing microcrystalline graphite with ammonium fluoride, carrying out fused salt roasting to convert impurities into part of soluble fluoride, and washing with deionized water to remove soluble impurities after roasting to obtain primarily purified graphite; and mixing the primarily purified graphite with deionized water, and stirring under a water bath condition to form ore pulp. Then adding aluminum salt and a complexing agent step by step in the ultrasonic treatment process for deep purification: firstly adding the aluminum salt to leach impurities, filtering and washing to be neutral, and then drying; and adding recovered ammonia water under an ultrasonic condition to adjust the pH value, adding a complexing agent to further remove impurities, and carrying out secondary filtration, washing and drying to obtain a high-purity graphite product. According to the method, efficient and green purification of graphite is realized through a step-by-step purification process and cyclic utilization of waste gas, and the fixed carbon content of the obtained high-purity graphite reaches 99.5% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing high-purity graphite by two-stage impurity removal through ultrasound-assisted coupling of aluminum salt and complexing agent, and belongs to the technical field of mineral processing and purification. Background Art

[0002] Microcrystalline graphite, a natural graphite with a high carbon content, is widely used in lithium-ion batteries, conductive materials, and high-temperature lubrication. However, natural microcrystalline graphite often contains impurities such as calcium and magnesium, which affect its electrochemical performance and purity. While traditional purification methods (such as hydrofluoric acid leaching) can effectively remove impurities, they pose challenges such as strong corrosiveness, high toxicity, and environmental pollution.

[0003] To reduce toxicity, researchers have attempted to treat alkali-melted graphite using a mixed acid consisting of hydrochloric acid, phosphoric acid, and ammonium fluoride. For example, patent CN102583342A first uses alkali calcination to prepare alkali-melted graphite, and then uses the mixed acid to further purify the graphite. However, because this treatment requires high-temperature calcination and a large amount of mixed acid, it results in high energy consumption and increases the difficulty of subsequent waste acid treatment. In addition to the above schemes, other approaches have been explored, such as patent CN104495803A, which describes a method for purifying natural microcrystalline graphite. The method comprises the following steps: 1) natural microcrystalline graphite is mixed with a 20% to 50% caustic soda solution, followed by grinding and calcination at 350-700°C while stirring the solution for reaction. The mixture is then pulverized and water-ground into a fine slurry. The solution and graphite are then separated, washed, and precipitated. The mixture is then filtered and dried to produce alkali-washed graphite. 2) the alkali-washed graphite, a soluble fluoride salt, and nitric acid are then added to a reaction vessel, heated, stirred, and impregnated. The solution and graphite are then separated to produce acid-containing graphite. 3) the acid-containing graphite is washed, precipitated, and filtered and dried to produce finished graphite. The soluble fluoride salt is sodium fluoride, ammonium fluoride, or ammonium difluoride. This patent also relies on high-temperature calcination and large amounts of highly concentrated acid, resulting in high energy consumption and increased difficulty in subsequent waste acid disposal. Summary of the Invention

[0004] In view of the high energy consumption, high risk and low environmental protection problems of the above-mentioned existing graphite purification methods, the present invention proposes a method for preparing high-purity graphite by two-stage impurity removal using ultrasound-assisted coupling of aluminum salt and complexing agent. That is, it replaces the traditional acid leaching process. When the pH is 2-3, aluminum salt is preferentially added. 3+ Hydrolysis under acidic conditions generates hydroxyaluminum complexes (such as Al(OH) 2+ ), adsorbing F through electrostatic interaction - , forming soluble Al-F complexes (such as AlF 3- ), further breaking the dissolution balance of CaF2 and MgF2. When the pH is 8-10, add a complexing agent such as EDTA. At this time, EDTA is in the form of Y4- Formal dominance, with Ca 2+ , Mg 2+ Form complexes with extremely high stability constants (lgK_{CaY} ≈ 10.7, lgK_{MgY} ≈ 8.7), completely eliminating the risk of re-precipitation of metal ions. And the invention introduces ultrasonic reinforcement means, using the microjet (~ 100 m / s) generated by ultrasonic cavitation to strip the impurity surface passivation layer, exposing the impurity to the solution, and improving the contact probability of complexing agents such as EDTA and metal ions. The present invention greatly improves the fixed carbon content of microcrystalline graphite, also reduces environmental impact and safety risk, and has wide application prospects.

[0005] The present application is a method for preparing high-purity graphite by ultrasonic-assisted two-stage impurity removal coupled with aluminum salt-complexing agent, comprising the following steps:

[0006] First, mix the microcrystalline graphite with ammonium fluoride and then perform roasting at 160℃~210℃ to convert the impurities into soluble fluorides. After roasting, remove the soluble impurities by washing to obtain the preliminary purified graphite. Mix the preliminary purified graphite with water at a certain solid-liquid ratio and stir to form a slurry under water bath conditions, at which time the slurry has a pH value of 2-5. Then, add aluminum salt and complexing agent step by step during ultrasonic treatment for deep purification: first, add aluminum salt to leach the impurities, filter and wash to neutral, and then dry; then, under ultrasonic conditions, add ammonia water to adjust the pH value, and add complexing agent to further remove impurities. After filtration (preferably multiple filtration, such as 2 times or more), washing and drying, high-purity graphite product is obtained. This method realizes efficient and green purification of graphite through a step-by-step purification process and recycling of waste gas.

[0007] In the present application, deionized water is used to wash and remove soluble impurities when obtaining the preliminary purified graphite. Of course, other solvents can also be used in the present application.

[0008] In the present application, the waste ammonia gas generated during the roasting process is prepared into ammonia water by water absorption for standby use.

[0009] In the present application, recovered ammonia water can be used to adjust the pH value before adding the complexing agent.

[0010] The present application is a method for preparing high-purity graphite by ultrasonic-assisted two-stage impurity removal coupled with aluminum salt-complexing agent, and the specific steps are as follows:

[0011] (1) Add ammonium fluoride to the microcrystalline graphite, mix and then perform molten salt roasting. After roasting, use deionized water to wash and remove soluble impurities. After water washing, dry by suction filtration to obtain the preliminary purified graphite sample A. The roasting temperature is 160℃~210℃.

[0012] (2) The gas (ammonia gas and hydrogen fluoride gas) generated in the roasting process of step (1) is introduced into a container containing water, and after adding quicklime, an ammonia water solution is obtained by filtration. In industrial applications, the addition of quicklime (CaO) can remove HCl and the like, and an ammonia water solution is obtained by filtration.

[0013] (3) The primary purified graphite sample A and deionized water are mixed in a certain proportion to obtain a slurry solution with a pH of 2.4-5.8, which is heated and stirred in a water bath, and ultrasonic treatment is added at the same time.

[0014] (4) During the ultrasonic treatment, after a period of leaching of the aluminum salt, filtration is performed, and after washing with water to neutralization, drying is performed to obtain a purified graphite sample B; wherein the graphite sample A and the aluminum salt are added in a certain molar ratio.

[0015] (5) The graphite sample B obtained in step (4) is mixed with deionized water according to the proportion of step (3), and the ammonia water solution obtained in step (2) is added to adjust the pH during ultrasonic treatment, and then a complexing agent is added for a period of leaching, and after filtration, washing with water to neutralization, and drying, a high-purity graphite C is obtained; wherein the graphite sample B and the complexing agent are added in a certain molar ratio.

[0016] The fixed carbon content of the microcrystalline graphite of step (1) is 80%-85%. The particle size D 50 is less than or equal to 20.2 microns.

[0017] The mixing mass ratio of the microcrystalline graphite of step (1) and ammonium fluoride is 1:1-1:2.5. In the process of technical exploration, other ammonium salts or fluorine salts have also been tried, but the effect is not ideal.

[0018] The roasting temperature of step (1) is 160-210°C, and the roasting time is 1-3h. In step (1) of the present application, the microcrystalline graphite is mixed with NH4F and roasted at 160-210°C, so that CaO, MgO impurities are converted into soluble fluorides and a small amount of insoluble CaF2 / MgF2. In the hot environment of 160-210°C, the hydrogen fluoride gas and ammonia gas generated by the decomposition of ammonium fluoride cooperate with the molten phase ammonium fluoride. HF preferentially penetrates the impurity grain boundary by topological chemical etching, so that alkaline earth metals (MgO, CaO) generate insoluble fluoride nanocrystals anchored on the surface of graphite, and Fe3O4 and NaO are converted into soluble fluorides. And the amphoteric oxide (SiO2, Al2O3) and sodium feldspar (NaAlSi3O8) generate soluble (NH4)3[AlF6] and (NH4)3[SiF6] under the joint action of ammonia gas and hydrogen fluoride gas.

[0019] The water washing temperature of step (1) is 50-65°C, and the time is 1.5-2.5h. The warm water washing can accelerate the dissolution rate of soluble impurities, increase the dissolution amount, and promote the dissolution of difficultly soluble fluorides (such as CaF2 and MgF2).

[0020] The fixed carbon content of graphite sample A in step (1) is 96.5-98%.

[0021] The concentration of the ammonia water solution in step (2) is 15-20%.

[0022] The mixing ratio of graphite sample A and deionized water in step (3) is 1:20-1:30 (g / ml).

[0023] The water bath heating temperature in step (3) is 60-70°C, and the reaction time is 1-2h.

[0024] The ultrasonic power in step (3) is 20-40 kHz, preferably 25-35 kHz.

[0025] The aluminum salt in step (4) is one of AlCl3, Al(NO3)3 and Al2(SO4)3, the molar ratio of graphite sample A and the aluminum salt is 1:1-1:1.6, and the leaching time is 60-120min.

[0026] The pH in step (5) is 8.1-10.6, the complexing agent is at least one of EDTA and citric acid, the molar ratio of graphite sample B and the complexing agent is 1:1-1:1.6, and the leaching time is 120-180min.

[0027] In the present application, the ultrasonic-assisted leaching is as follows: the calcined product is added with an aluminum salt (such as AlCl3) under an acidic (pH 2-5) condition, [AlF6] 3- complexes and dissolves the residual fluoride, the pH is adjusted to 8-10, EDTA is introduced to selectively complex Ca 2+ / Mg 2+ ;

[0028] In the present application, the ultrasonic intensification is preferably the application of ultrasonic waves (20-40 kHz) throughout the whole process, which can destroy the impurity coating and improve the reaction kinetics.

[0029] In the present application, the ammonium fluoride is decomposed to produce NH3 and HF during the molten salt calcination, HF reacts with metal impurities (Ca, Mg, etc.) in the graphite to generate difficultly soluble fluorides (such as CaF2 and MgF2) and part of soluble fluorides. In the acidic environment of pH 2-5, the aluminum salt (such as AlCl3) dissociates Al 3+ from the F - in the difficultly soluble fluorides (CaF2 and MgF2) to form stable [AlF6]3- Complex ions are removed by water washing. The ultrasonic cavitation effect further destroys the impurity coating layer and accelerates the mass transfer process. Then, by adjusting the pH to alkaline (8-10) with recovered ammonia water, the carboxyl groups in EDTA or citric acid form high-stability chelates (such as [Ca-EDTA] 2+ , Mg 2+ form high-stability chelates (such as [Ca-EDTA] 2- , lgK = 10.7), and the ultrasonic effect promotes the diffusion of the complexing agent to the interlayer of graphite, improving the reaction efficiency.

[0030] As a preferred solution, the present application provides a method for preparing high-purity graphite by ultrasonic-assisted two-stage impurity removal coupled with aluminum salt-complexing agent, and the specific steps are as follows:

[0031] (1) Mix microcrystalline graphite with a fixed carbon content of 80-85% and ammonium fluoride at a mass ratio of 1:1-1.3, and then perform molten salt roasting at 160-190°C for 2.5-3h. After roasting, water wash at 55-60°C for 1.5-2h to remove soluble impurities, and then vacuum filtration and drying to obtain a preliminary purified graphite sample A; the particle size D 50 = 17-21 microns of the microcrystalline graphite;

[0032] (2) Pass the ammonia gas generated during the roasting process of step (1) into a gas collection bottle containing water to obtain an ammonia water solution with a concentration of

[0033] (3) Mix the preliminary purified graphite sample A with deionized water at a solid-liquid ratio (g / ml) of 1:20-22 to obtain a slurry solution with a pH of 4.5-5.8, and then perform water bath stirring and heating at a temperature of 60-65°C for 1.2-1.8h, while performing intensive treatment at an ultrasonic power of 25-33kHz;

[0034] (4) During the ultrasonic treatment process, add Al(NO3)3 and leach for 90-120min, then filter, wash with water to neutralize, and dry to obtain a purified graphite sample B; wherein the graphite sample A and Al(NO3)3 are added at a molar ratio of 1:1.3-1.4.

[0035] (5) Mix the graphite sample B obtained in step (4) with deionized water according to the ratio of step (3), adjust the pH to 8.5-10.6 by adding ammonia water during the ultrasonic treatment process, and then add a complexing agent and leach for 120-170min, then filter, wash with water to neutralize, and dry to obtain high-purity graphite C; wherein the graphite sample B and the complexing agent are added at a molar ratio of 1:1-1.3; the complexing agent is citric acid or EDTA.

[0036] The present application has the following advantages:

[0037] (1) Through the three-stage purification system of "fluorination roasting-acidic aluminum salt complexation-alkaline chelation", the purity of graphite can be increased to more than 99.5%, especially the removal rate of insoluble CaF2 and MgF2 is >98%, which is better than the traditional acid leaching method (85-90%).

[0038] (2) NH4F is used to replace hydrofluoric acid, and the NH3 in the roasting waste gas is recycled as ammonia water;

[0039] (3) The toxicity of the aluminum salt / EDTA system is much lower than that of hydrofluoric acid, and the wastewater can meet the discharge standards after simple neutralization;

[0040] (4) Ultrasonic assistance reduces the reaction temperature (60-80°C), shortening the process time by 50%.

[0041] (5) Ultrasonic enhancement and the use of a coupled aluminum salt-complexing agent to remove impurities resulted in a final graphite product with a finer particle size (less than 12.5 μm) and a significantly increased specific surface area (4.68 → 9.94 m² / g or even higher), providing an ideal interface for enhanced ion / electron transport. Furthermore, scanning electron microscopy revealed that the graphite flakes were intact and regularly arranged, presumably due to the removal of calcium fluoride and magnesium fluoride. The entire process is acid-free and alkaline-free, completely eliminating acid-base wastewater pollution. The overall energy consumption is reduced by 67% compared to the traditional acid method, in line with the goal of carbon neutrality. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Attachment Figure 1 This is a characterization diagram of the laser particle size and specific surface area of ​​the graphite products in Example 4 and Example 6.

[0043] Attachment Figure 2 This is the SEM image of the graphite product in Example 2.

[0044] Figure 1 Composed of a, b, c, d, wherein a and c are characterization diagrams of the product obtained in Example 4; b and d are characterization diagrams of the product obtained in Example 6. Figure 1 It can be seen that the particle size of the products of Examples 4 and 6.

[0045] from Figure 2 The product morphology of Example 2 can be seen. DETAILED DESCRIPTION

[0046] The present invention will be further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the contents described above.

[0047] Example 1: A method for preparing high-purity graphite by two-stage impurity removal using ultrasound-assisted coupling of aluminum salt and complexing agent, the specific steps are as follows:

[0048] (1) Microcrystalline graphite with a fixed carbon content of 81% (particle size D 50= 19.8 microns, specific surface area 4.68 m 2 / g) and ammonium fluoride in a mass ratio of 1:2 were mixed and then subjected to molten salt roasting at 170°C for 1.5h. After roasting, the sample was washed with water at 65°C for 1.7h to remove soluble impurities. After washing, the sample was filtered and dried to obtain a preliminary purified graphite sample A. At this time, the fixed carbon content of the graphite sample A was 98%.

[0049] (2) The ammonia gas generated during the roasting process of step (1) was introduced into a gas collection bottle containing 210ml of deionized water to obtain an ammonia water solution with a concentration of 18%.

[0050] (3) The preliminary purified graphite sample A and deionized water were mixed in a solid-liquid ratio (g / ml) of 1:25 to obtain a slurry solution with a pH of 5.3. Then, the slurry solution was heated in a water bath at 68°C for 2h while being subjected to intensive treatment at an ultrasonic power of 35kHz.

[0051] (4) During the ultrasonic treatment, Al(NO3)3 was added and leached for 60min. After filtration, the sample was washed with water until neutral and then dried to obtain a purified graphite sample B. The molar ratio of the graphite sample A to Al(NO3)3 was 1:1.6.

[0052] (5) The graphite sample B obtained in step (4) was mixed with deionized water in the same ratio as step (3). During the ultrasonic treatment, ammonia water was added to adjust the pH to 9.2. Then, EDTA was added and leached for 130min. After filtration, the sample was washed with water until neutral and then dried to obtain high-purity graphite C. The molar ratio of the graphite sample B to EDTA was 1:1.3.

[0053] The high-purity graphite obtained in this embodiment had a fixed carbon content of 99.6%, a particle size D 50 = 10.5 microns, and a specific surface area of 9.94 m 2 / g.

[0054] Example 2: A method for preparing high-purity graphite by ultrasonic-assisted two-stage impurity removal coupled with aluminum salt and complexing agent, the specific steps are as follows:

[0055] (1) Microcrystalline graphite with a fixed carbon content of 80% (particle size D 50 = 17.4 microns) and ammonium fluoride were mixed in a mass ratio of 1:1.3. Then, the mixture was subjected to molten salt roasting at 160°C for 3h. After roasting, the sample was washed with water at 57°C for 1.9h to remove soluble impurities. After washing, the sample was filtered and dried to obtain a preliminary purified graphite sample A. At this time, the fixed carbon content of the graphite sample A was 97.8%.

[0056] (2) The ammonia gas generated during the roasting process of step (1) was introduced into a gas collection bottle containing 250ml of deionized water to obtain an ammonia water solution with a concentration of 15%.

[0057] (3) The preliminary purified graphite sample A and deionized water are mixed at a solid-liquid ratio of 1:22 (g / ml) to obtain a slurry solution with a pH of 5.8, and then heated in a water bath at 64°C for 1.8h while being treated with enhanced ultrasound at a power of 33 kHz.

[0058] (4) During the ultrasound treatment, Al(NO3)3 is added and leached for 90 min, then filtered, washed with water to neutral, and dried to obtain purified graphite sample B; wherein the molar ratio of graphite sample A to Al(NO3)3 is 1:1.3.

[0059] (5) The graphite sample B obtained in step (4) is mixed with deionized water according to the ratio of step (3), and an ammonia solution is added to adjust the pH to 10.6 during the ultrasound treatment, and then citric acid is added and leached for 170 min, then filtered, washed with water to neutral, and dried to obtain high-purity graphite C; wherein the molar ratio of graphite sample B to citric acid is 1:1.

[0060] The high-purity graphite obtained in this embodiment has a fixed carbon content of 99.7%, a particle size D 50 =8.8 microns, and a specific surface area of 11.6 m 2 / g.

[0061] Example 3: A method for preparing high-purity graphite by ultrasound-assisted two-stage impurity removal coupled with aluminum salt and complexing agent, the specific steps are as follows:

[0062] (1) Microcrystalline graphite with a fixed carbon content of 84% (particle size D 50 =20.2 microns) and ammonium fluoride are mixed at a mass ratio of 1:1, and then subjected to molten salt roasting at 190°C for 2.5h. After roasting, the soluble impurities are removed by water washing at 60°C for 1.5h. After water washing, the mixture is filtered and dried to obtain a preliminary purified graphite sample A. At this time, the fixed carbon content of the graphite sample A is 97.5%.

[0063] (2) The ammonia gas generated during the roasting process in step (1) is introduced into a gas collection bottle containing 230 ml of deionized water to obtain an ammonia water solution with a concentration of 16%.

[0064] (3) The preliminary purified graphite sample A and deionized water are mixed at a solid-liquid ratio of 1:20 (g / ml) to obtain a slurry solution with a pH of 4.5, and then heated in a water bath at 60°C for 1.2h while being treated with enhanced ultrasound at a power of 25 kHz.

[0065] (4) During the ultrasound treatment, AlCl3 is added and leached for 120 min, then filtered, washed with water to neutral, and dried to obtain purified graphite sample B; wherein the molar ratio of graphite sample A to AlCl3 is 1:1.4.

[0066] (5) The graphite sample B obtained in step (4) is mixed with deionized water in the proportion of step (3), and an ammonia solution is added to adjust the pH to 8.5 during ultrasonic treatment, and then EDTA is added to leach for 120 min, and then filtered, washed with water to neutral, and dried to obtain high-purity graphite C; wherein the graphite sample B and EDTA are added in a molar ratio of 1:1.2.

[0067] The high-purity graphite obtained in this embodiment has a fixed carbon content of 99.5%, a particle size D 50 =9.9 microns, and a specific surface area of 10.2 m 2 / g.

[0068] Example 4: A method for preparing high-purity graphite by ultrasonic-assisted coupling of aluminum salt-complexing agent two-stage impurity removal, the specific steps are as follows:

[0069] (1) Microcrystalline graphite with a fixed carbon content of 83% (particle size D 50 =17.6 microns) and ammonium fluoride are mixed in a mass ratio of 1:1.6, and then subjected to molten salt roasting at 180°C for 1h. After roasting, water washing is performed at 50°C for 2.3h to remove soluble impurities. After water washing, the sample is filtered and dried to obtain a preliminary purified graphite sample A. At this time, the fixed carbon content of the graphite sample A is 96.5%.

[0070] (2) The ammonia gas generated during the roasting process in step (1) is introduced into a gas collection bottle containing 150ml of deionized water to obtain an ammonia water solution with a concentration of 20%.

[0071] (3) The preliminary purified graphite sample A and deionized water are mixed in a solid-liquid ratio of 1:28 (g / ml) to obtain a slurry solution with a pH of 2.4, and then heated in a water bath at 62°C for 1h while being subjected to intensive treatment at an ultrasonic power of 26kHz.

[0072] (4) During ultrasonic treatment, AlCl3 is added to leach for 110 min, and then filtered, washed with water to neutral, and dried to obtain a purified graphite sample B; wherein the graphite sample A and AlCl3 are added in a molar ratio of 1:1.

[0073] (5) The graphite sample B obtained in step (4) is mixed with deionized water in the proportion of step (3), and an ammonia solution is added to adjust the pH to 8.1 during ultrasonic treatment, and then citric acid is added to leach for 160 min, and then filtered, washed with water to neutral, and dried to obtain high-purity graphite C; wherein the graphite sample B and citric acid are added in a molar ratio of 1:1.6.

[0074] The high-purity graphite obtained in this embodiment has a fixed carbon content of 99.6%, a particle size D 50 =11.4 microns, and a specific surface area of 7.7 m 2 / g.

[0075] Example 5: A method for preparing high-purity graphite by ultrasonic-assisted coupling of aluminum salt-complexing agent two-stage impurity removal, the specific steps are as follows:

[0076] (1) The microcrystalline graphite with a fixed carbon content of 82% (particle size D 50 = 16.9 microns) and ammonium fluoride were mixed in a mass ratio of 1:1.8, and then subjected to molten salt roasting at 210°C for 1.8h. After roasting, the soluble impurities were removed by water washing at 63°C for 2.5h. After water washing, the preliminary purified graphite sample A was obtained by suction filtration and drying. At this time, the fixed carbon content of the graphite sample A was 96.9%.

[0077] (2) The ammonia gas generated during the roasting process of step (1) was introduced into a gas collection bottle containing 200ml of deionized water to obtain an ammonia water solution with a concentration of 19%.

[0078] (3) The preliminary purified graphite sample A and deionized water were mixed in a solid-liquid ratio (g / ml) of 1:30 to obtain a slurry solution with a pH of 3.2. Then, the slurry solution was heated in a water bath at 70°C for 1.3h while being subjected to ultrasonic treatment at a power of 30kHz.

[0079] (4) During the ultrasonic treatment, Al2(SO4)3 was added and leached for 80min, then filtered, washed with water until neutral, and dried to obtain the purified graphite sample B. The molar ratio of the graphite sample A to Al2(SO4)3 was 1:1.5.

[0080] (5) The graphite sample B obtained in step (4) was mixed with deionized water in the same ratio as step (3), and ammonia water was added during the ultrasonic treatment to adjust the pH to 10.3. Then, EDTA was added and leached for 180min, then filtered, washed with water until neutral, and dried to obtain high-purity graphite C. The molar ratio of the graphite sample B to EDTA was 1:1.4.

[0081] The high-purity graphite obtained in this embodiment had a fixed carbon content of 99.7%, a particle size D 50 = 13.7 microns, and a specific surface area of 10.4m 2 / g.

[0082] Example 6: A method for preparing high-purity graphite by ultrasonic-assisted coupling of aluminum salt-complexing agent two-stage impurity removal, the specific steps are as follows:

[0083] (1) The microcrystalline graphite with a fixed carbon content of 85% (particle size D 50 = 18.3 microns) and ammonium fluoride were mixed in a mass ratio of 1:2.5, and then subjected to molten salt roasting at 200°C for 2h. After roasting, the soluble impurities were removed by water washing at 55°C for 2h. After water washing, the preliminary purified graphite sample A was obtained by suction filtration and drying. At this time, the fixed carbon content of the graphite sample A was 97.2%.

[0084] (2) The ammonia gas produced in the roasting process of step (1) is passed into a gas collecting bottle containing 180 ml of deionized water to obtain an ammonia water solution with a concentration of 17%.

[0085] (3) The preliminary purified graphite sample A and deionized water are mixed at a solid-liquid ratio (g / ml) of 1:24 to obtain a slurry solution with a pH of 2.9, which is then heated in a water bath at 65°C for 1.5 h while being intensively treated with an ultrasonic power of 28 kHz.

[0086] (4) During the ultrasonic treatment, Al2(SO4)3 is added and leached for 100 min, then filtered, washed with water to neutral, and dried to obtain the purified graphite sample B; wherein the graphite sample A and Al2(SO4)3 are added at a molar ratio of 1:1.2.

[0087] (5) The graphite sample B obtained in step (4) is mixed with deionized water according to the ratio of step (3), and an ammonia water solution is added to adjust the pH to 9.7 during the ultrasonic treatment, and then citric acid is added and leached for 150 min, then filtered, washed with water to neutral, and dried to obtain high-purity graphite C; wherein the graphite sample B and citric acid are added at a molar ratio of 1:1.5.

[0088] The high-purity graphite obtained in this embodiment has a fixed carbon content of 99.8%, a particle size D 50 =12.3 microns, and a specific surface area of 7.3 m 2 / g.

[0089] Comparative Example 1: The conditions are the same as those of Example 1, except that step 5 of Example 1 is omitted; that is, the specific steps are as follows:

[0090] (1) Microcrystalline graphite with a fixed carbon content of 81% (particle size D 50 =19.8 microns) and ammonium fluoride are mixed at a mass ratio of 1:2, and then molten salt roasting is performed at 170°C for 1.5 h, after which water washing is performed at 65°C for 1.7 h to remove soluble impurities, and then the water-washed and dried sample is obtained as the preliminary purified graphite sample A; at this time, the fixed carbon content of the graphite sample A is 98%.

[0091] (2) The ammonia gas produced in the roasting process of step (1) is passed into a gas collecting bottle containing 210 ml of deionized water to obtain an ammonia water solution with a concentration of 18%.

[0092] (3) The preliminary purified graphite sample A and deionized water are mixed at a solid-liquid ratio (g / ml) of 1:25 to obtain a slurry solution with a pH of 5.3, which is then heated in a water bath at 68°C for 2 h while being intensively treated with an ultrasonic power of 35 kHz.

[0093] (4) During the ultrasonic treatment, after leaching for 60 min with Al(NO3)3, the graphite sample A was filtered, washed with water until neutral, and dried to obtain purified graphite B; wherein the graphite sample A and Al(NO3)3 were added in a molar ratio of 1:1.6.

[0094] The purified graphite obtained in the present comparative example has a fixed carbon content of 98.7%, a particle size D 50 = 14.8 microns, and a specific surface area of 6.2 m 2 / g.

[0095] Comparative Example 2: The conditions are the same as those in Example 3, except that the ultrasonic treatment in Example 3 is omitted; that is, the specific steps are as follows:

[0096] (1) Microcrystalline graphite with a fixed carbon content of 84% (particle size D 50 = 20.2 microns) and ammonium fluoride were mixed in a mass ratio of 1:1, and then subjected to molten salt roasting at 190°C for 2.5 h. After roasting, the sample was washed with water at 60°C for 1.5 h to remove soluble impurities, and then filtered and dried to obtain a preliminary purified graphite sample A. At this time, the fixed carbon content of the graphite sample A was 97.5%.

[0097] (2) Ammonia gas generated during the roasting process in step (1) was introduced into a gas collection bottle containing 230 ml of deionized water to obtain an ammonia water solution with a concentration of 16%.

[0098] (3) The preliminary purified graphite sample A and deionized water were mixed in a solid-liquid ratio (g / ml) of 1:20 to obtain a slurry solution with a pH of 4.5, and then heated in a water bath at 60°C for 1.2 h.

[0099] (4) AlCl3 was added to the slurry solution of step (2) and leached for 120 min, and then filtered, washed with water until neutral, and dried to obtain a purified graphite sample B; wherein the graphite sample A and AlCl3 were added in a molar ratio of 1:1.4.

[0100] (5) The graphite sample B obtained in step (4) was mixed with deionized water in the same ratio as step (3), and the pH was adjusted to 8.5 by adding an ammonia water solution. Then, EDTA was added and leached for 120 min, and then filtered, washed with water until neutral, and dried to obtain a purified graphite C; wherein the graphite sample B and EDTA were added in a molar ratio of 1:1.2.

[0101] The purified graphite obtained in the present comparative example has a fixed carbon content of 98.2%, a particle size D 50 = 15.3 microns, and a specific surface area of 5.1 m 2 / g.

[0102] Comparative Example 3: The conditions are the same as those in Example 6, except that step 4 in Example 6 is omitted; that is, the specific steps are as follows:

[0103] (1) Microcrystalline graphite (particle size D 50 = 18.3 microns) with a fixed carbon content of 85% and ammonium fluoride were mixed in a mass ratio of 1:2.5, and then molten salt roasting was performed at 200°C for 2h. After roasting, water washing was performed at 55°C for 2h to remove soluble impurities. After water washing, the sample was filtered and dried to obtain a preliminary purified graphite sample A. At this time, the fixed carbon content of the graphite sample A was 97.2%.

[0104] (2) Ammonia gas generated during the roasting process of step (1) was introduced into a gas collection bottle containing 180ml of deionized water to obtain an ammonia water solution with a concentration of 17%.

[0105] (3) The preliminary purified graphite sample A and deionized water were mixed in a solid-liquid ratio (g / ml) of 1:24 to obtain a slurry solution with a pH of 2.9. Then, the slurry solution was heated in a water bath at 65°C for 1.5h while being intensively treated with ultrasonic power of 28kHz.

[0106] (4) During the ultrasonic treatment, the pH was adjusted to 9.7 by adding an ammonia water solution. Then, citric acid was added and leaching was performed for 150min. After filtration, the sample was washed with water until neutral, and then dried to obtain a purified graphite sample B. The molar ratio of the graphite sample A to the citric acid was 1:1.5.

[0107] The purified graphite obtained in the present comparative example had a fixed carbon content of 98.1%, a particle size D 50 = 16.4 microns, and a specific surface area of 5.7m 2 / g.

[0108] The above detailed the specific embodiments of the present application, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge of those skilled in the art without departing from the spirit of the present application.

Claims

1. A method for preparing high-purity graphite by two-stage impurity removal using ultrasound-assisted coupling of aluminum salt and complexing agent, characterized in that: The method includes the following steps: First, microcrystalline graphite is mixed with ammonium fluoride and then calcined at 160°C to 210°C to convert impurities into soluble fluorides. After calcination, the soluble impurities are removed by washing to obtain preliminarily purified graphite. The preliminarily purified graphite is then mixed with water at a certain solid-liquid ratio and stirred in a water bath to form a slurry. At this time, the slurry has a pH value of 2-5. Subsequently, aluminum salts and complexing agents are added step by step during the ultrasonic treatment process for deep purification: aluminum salts are first added to leach out impurities, and the mixture is filtered and washed to neutrality and then dried; then ammonia water is added under ultrasonic conditions to adjust the pH, and a complexing agent is added to further remove impurities. After filtering, washing and drying, a high-purity graphite product is obtained; the purity of the high-purity graphite product is greater than or equal to 99.5%.

2. The method for preparing high-purity graphite by ultrasonic-assisted coupling aluminum salt-complexing agent two-stage impurity removal according to claim 1, characterized in that: The method includes the following steps: (1) Ammonium fluoride was added to microcrystalline graphite, mixed and then calcined in molten salt. After calcination, the sample was washed with deionized water to remove soluble impurities. After washing, the sample was filtered and dried to obtain a preliminary purified graphite sample A. The calcination temperature was 160°C~210°C. (2) passing the gas generated during the roasting process in step (1) into a container filled with water, adding quicklime, and filtering to obtain an ammonia solution; (3) Preliminary purified graphite sample A and deionized water were mixed in a certain proportion to obtain a slurry solution with a pH of 2.4 to 5.8, which was then placed in a water bath for heating and stirring, while ultrasonic treatment was added for enhanced treatment; (4) During the ultrasonic treatment, aluminum salt is added and leached for a period of time, filtered, washed with water until neutral, and then dried to obtain purified graphite sample B; wherein graphite sample A and aluminum salt are added in a certain molar ratio; (5) The graphite sample B obtained in step (4) is mixed with deionized water in the proportion of step (3), and the ammonia solution obtained in step (2) is added during the ultrasonic treatment to adjust the pH, and then a complexing agent is added to leach for a period of time, filtered, washed with water until neutral, and then dried to obtain high-purity graphite C; wherein the graphite sample B and the complexing agent are added in a certain molar ratio.

3. The method for preparing high-purity graphite by ultrasonic-assisted coupling aluminum salt-complexing agent two-stage impurity removal according to claim 2, characterized in that: The fixed carbon content of the microcrystalline graphite in step (1) is 80% to 85%. Its particle size D 50 Less than or equal to 20.2 microns.

4. The method for preparing high-purity graphite by ultrasonic-assisted coupling aluminum salt-complexing agent two-stage impurity removal according to claim 2, characterized in that: The mass ratio of the microcrystalline graphite and ammonium fluoride in step (1) is 1:1 to 1:2.

5.

5. The method for preparing high-purity graphite by ultrasonic-assisted coupling aluminum salt-complexing agent two-stage impurity removal according to claim 2, characterized in that: The roasting temperature of step (1) is 160°C to 210°C, and the roasting time is 1 to 3 hours; The water washing temperature in step (1) is 50°C to 65°C, and the washing time is 1.5 to 2.5 hours.

6. The method for preparing high-purity graphite by ultrasonic-assisted coupling aluminum salt-complexing agent two-stage impurity removal according to claim 2, characterized in that: The fixed carbon content of the graphite sample A in step (1) is 96.5% to 98%.

7. The method for preparing high-purity graphite by ultrasonic-assisted coupling aluminum salt-complexing agent two-stage impurity removal according to claim 2, characterized in that: In terms of g / ml, the mixing ratio of the graphite sample A and deionized water in step (3) is 1:20 to 1:30; The water bath heating temperature in step (3) is 60-70°C, and the reaction time is 1h-2h; The ultrasonic power of step (3) is 20-40 kHz, preferably 25-35 kHz.

8. The method for preparing high-purity graphite by ultrasonic-assisted coupling aluminum salt-complexing agent two-stage impurity removal according to claim 2, characterized in that: The aluminum salt in step (4) is one of AlCl3, Al(NO3)3, and Al2(SO4)3, the molar ratio of graphite sample A and aluminum salt is 1:1~1:1.6, and the leaching time is 60~120min.

9. The method for preparing high-purity graphite by ultrasonic-assisted coupling aluminum salt-complexing agent two-stage impurity removal according to claim 2, characterized in that: The pH of step (5) is 8.1-10.6, the complexing agent is at least one of EDTA and citric acid, the molar ratio of graphite sample B and complexing agent is 1:1-1:1.6, and the leaching time is 120-180 min.

10. The method for preparing high-purity graphite by two-stage impurity removal using ultrasound-assisted coupling of aluminum salt and complexing agent according to claim 2, characterized in that: The method includes the following steps: (1) Microcrystalline graphite with a fixed carbon content of 80-85% and ammonium fluoride were mixed in a mass ratio of 1:1-1.3, and then calcined in molten salt at 160-190°C for 2.5-3h. After calcination, the mixture was washed with water at 55-60°C for 1.5-2h to remove soluble impurities. After washing with water, the mixture was filtered and dried to obtain a preliminary purified graphite sample A. The particle size of the microcrystalline graphite was D 50 =17~21 μm; (2) passing the ammonia gas generated during the roasting process of step (1) into a gas collecting bottle filled with water to obtain an ammonia solution with a concentration of 1. (3) Preliminary purified graphite sample A and deionized water were mixed at a solid-liquid ratio of 1:20-22 (g / ml) to obtain a slurry solution with a pH of 4.5-5.8, and then stirred and heated in a water bath at 60-65°C for 1.2-1.8 h, while performing enhanced ultrasonic treatment at a power of 25-33 kHz; (4) During the ultrasonic treatment, Al(NO3)3 was added and leached for 90-120 min, then filtered, washed with water until neutral, and dried to obtain purified graphite sample B; wherein graphite sample A and Al(NO3)3 were added at a molar ratio of 1:1.3-1.4; (5) The graphite sample B obtained in step (4) is mixed with deionized water in the proportion of step (3), and an ammonia solution is added during ultrasonic treatment to adjust the pH to 8.5-10.

6. Then, a complexing agent is added and leached for 120-170 minutes, filtered, washed with water until neutral, and then dried to obtain high-purity graphite C; wherein the graphite sample B and the complexing agent are added in a molar ratio of 1:1-1.3; the complexing agent is citric acid or EDTA.

Citation Information

Patent Citations

  • Purification method of microcrystal graphite

    CN102583342A

  • Purification method of natural microcrystalline graphite

    CN104495803A